Settler Witnessing at the Truth and Reconciliation Commission of Canada - Nagy, Rosemary (Hum Rights Rev, 2020)
This article offers an account of settler witnessing of residential school survivor testimony that avoids the politics of recognition and the pitfalls of colonial empathy. It knits together the concepts of bearing witness, Indigenous storytelling, and affective reckoning. Following the work of Kelly Oliver, it argues that witnessing involves a reaching beyond ourselves and responsiveness to the agency and self-determination of the other. Given the cultural genocide of residential schools, responsiveness to the other require openness to and nurturing of Indigenous ways of knowing and being. In order to illustrate the complexities and challenges of settler witnessing, the author reflects on her experiences in attending six of the TRC’s national events and, in particular, what she has learned from Frederick “Fredda” Paul, Passamaquoddy Elder, healer, storyteller, and residential school survivor. The article analyzes (1) aesthetics and emotions in the staging of TRC events and (2) making meaning over time and the temporality of transitional justice.